A Scholar Knows No Boundary in Time: An Interview with Avgusta Malinkovskaya - Augusta V. Malinkovskaya; Margarita A. Bukrinskaya (Современные проблемы музыкознания)
Avgusta V. Malinkovskaya, Doctor of Pedagogy, is Professor at the Department of Pedagogy and Methodology, Gnesin Russian Academy of Music. She did her graduate and post-graduate studies at Gnesin State Musical and Pedagogical Institute and was a student of Prof. Elena F. Gnesina. In 1966, she began teaching at the Department of Special Piano and the Department of Pedagogy and Teaching Methodology. In 2010–2015, she headed the Department of Teaching Methodology and Pedagogical Practice. For many decades, Prof. Malinkovskaya has been actively engaged in creativity, teaching and research. She supervises research projects of students, trainees, and doctoral students. She is a regular speaker at international academic events. Prof. Malinkovskaya is the author of numerous articles on the history, theory and methods of teaching the art of piano playing. She also explores issues related to piano intonation and has produced a dozen of textbooks and teaching aids. She also authored two scholarly monographs about BelaBartok: Bartok's Microcosmos and Bela Bartok—the Teacher. In her interview, Prof. Malinkovskaya speaks about her childhood, the hobbies of her early youth, her development as a musician, teacher and scholar, and about the Gnesin school which shaped her life and her career. She also shares her teaching experience with Margarita A. Bukrinskaya, a former student and now Associate Professor of the Gnesin Russian Academy of Music.